DEVELOPMENT OF A WEBSITE-BASED “CIRCUITPINTAR” TO IMPROVE THE COMPETENCIES OF THE ELECTRICAL INSTALLATION ENGINEERING STUDENTS - Dea Putri Nurwahyunita; Subuh Isnur Haryudo; Rina Harimurti; Ali Nur Fathoni (Universitas Labuhanbatu, 2026)
Purpose – This study aimed to develop and evaluate CircuitPintar, a website-based learning medium designed to improve the competencies of vocational high school students in the Basic Electrical Theory element of the Electrical Installation Engineering program.Methodology – The research employed a Research and Development approach using the ADDIE model: analysis, design, development, implementation, and evaluation. The implementation trial involved 35 Grade X TITL students at SMKN 3 Surabaya. Data were collected through media and material validation sheets, teacher and student response questionnaires, a 25-item cognitive test, and psychomotor and affective observation rubrics. Data were analyzed using percentage-based validity and practicality criteria, Shapiro-Wilk normality tests, paired-sample t-tests, and normalized gain (N-gain).Findings – CircuitPintar was categorized as highly valid in media validation (91%) and material validation (94%). Practicality was also high, with teacher responses of 91% and student responses of 86%. Students’ mean scores increased from 72.74 to 88.17 in the cognitive domain, from 71.77 to 88.74 in the psychomotor domain, and from 73.40 to 88.00 in the affective domain. All improvements were statistically significant (p < 0.001), and N-gain values for all domains were in the moderate category.Contribution – This study presents an empirically tested model of website-based vocational learning media that combines concept mastery and virtual practice on a single platform, offering a practical reference for developing similar digital media for other technical and vocational subjects.